Are short-lived jobs stepping stones to long-lasting jobs? - Bart Leo Wim Cockx; Matteo Picchio (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper assesses whether short-lived jobs (lasting one quarter or less and involuntarily ending in unemployment) are stepping stones to long-lasting jobs (enduring one year or more) for Belgian long-term unemployed school-leavers. We proceed in two steps. First, we estimate labour market trajectories in a multi-spell duration model that incorporates lagged duration and lagged occurrence dependence. Second, in a simulation we find that (fe)male school-leavers accepting a short-lived job are, within two years, 13.4 (9.5) percentage points more likely to find a long-lasting job than in the counterfactual in which they reject short-lived jobs.
Keywords: C15; C41; J62; J64; 330; Event history model; transition data; state dependence; short-lived jobs; stepping stone effect; long-lasting jobs; Absolventen; Langzeitarbeitslosigkeit; Berufliche Integration; Befristeter Arbeitsvertrag; Arbeitsverhältnis; Arbeitsplatzsicherung; Belgien